The concept of mindfulness: nonspecific factor of psychological wellbeing - Pugovkina O.D.; Shil'nikova Z. (Современная зарубежная психология, 2015)
During the last decades the growing interest in the study of the concept of mindfulness as a psychological construct and a form of psychotherapeutic intervention for the prevention and treatment of various mental disorders has become prominent in the foreign literature. On the basis of empirical evidence the article describes the positive effects of psychological awareness, including an increase of the subjective well-being, satisfaction with interpersonal relationships, improvement of some cognitive performance (working memory, executive functions), decline in cognitive and emotional reactivity. The article gives a description of the presumed neurobiological correlates of awareness and formulate the general perspective for further research.